Measurement of associated production of vector bosons and top quark-antiquark pairs in pp collisions at √s=7 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Aguilo, E.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; et al. (AMER PHYSICAL SOC, 2013)
The first measurement of vector-boson production associated with a top quark-antiquark pair in proton-proton collisions at root s = 7 TeV is presented. The results are based on a data set corresponding to an integrated luminosity of 5.0 fb(-1), recorded by the CMS detector at the LHC in 2011. The measurement is performed in two independent channels through a trilepton analysis of t (t) over barZ events and a same-sign dilepton analysis of t (t) over barV (V = W or Z) events. In the trilepton channel a direct measurement of the t (t) over barZ cross section sigma(t (t) over barZ) = 0.28(-0.11)(+0.14) (stat)(-0.03)(+0.06) (syst) pb is obtained. In the dilepton channel a measurement of the t (t) over barV cross section yields sigma(t (t) over barV) = 0.43(-0.15)(+0.17) (stat)(-0.07)(+0.09) (syst) pb. These measurements have a significance, respectively, of 3.3 and 3.0 standard deviations from the background hypotheses and are compatible, within uncertainties, with the corresponding next-to-leading order predictions of 0.137(-0.016)(+0.012) and 0.306(-0.053)(+0.031) pb. DOI: 10.1103/PhysRevLett.110.172002
Keywords: Physics